Micronutrient Therapy for Chronic Pancreatitis: Premises and Pitfalls - Braganza, Joan Marie (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: The first home of the Medical School of University of Manchester, United Kingdom (as seen in 1908).